Problem Based Learning Assisted by Mind Mapping: Solution to Improve Science Critical Thinking Abilities - Pradnyani, Putu Sagita; Wibawa, I Made Citra; Asril, Nice Maylani (Undiksha Press, 2023)
The ability to think critically is one of the required skills that must be possessed by 21st century students. However, existing learning in schools still does not use learning models that are able to hone students' thinking abilities and does not involve students actively in learning material in class. This research aims to determine the effect of using the Problem Based Learning model assisted by mind mapping on critical thinking skills in science in class V students. The population in this research is class V elementary school students. The sample was selected using a random sampling technique where the experimental class consisted of 30 students and the control class consisted of 26 students. The data collection method in this research uses a test method with 30 questions. The data obtained was then analyzed using the t-test. Based on the results of data analysis, tcount (1.743) is greater than ttable (1.297), so it can be concluded that H0 is rejected and H1 is accepted. It was concluded that there was an influence of the Problem Based Learning (PBL) learning model assisted by mind mapping on the science critical thinking abilities of fifth grade elementary school students.